Malaysian English Monophthongs by Regional Malay Dialect Speakers: Convergence or Divergence? - Sulong, Suhaila (Asiatic: IIUM Journal of English Language and Literature, 2016)
This study investigates the possible influence of Malay regional dialects on Malaysian English monophthongs. It compares the production of Malay and English monophthongs by male and female speakers of Standard Malay, Terengganu Malay and Kelantan Malay. Formant and Euclidean distance measurements show that although there are significant variations in Malay monophthong production, the speakers’ English monophthongs tend to converge spectrally. Two second language phonology theories are used to explain the results.